Affective salience can reverse the effects of stimulus-driven salience on eye movements in complex scenes - Niu, Yaqing; Todd, Rebecca; Anderson, Adam K. (Frontiers in Psychology, 2012)
In natural vision both stimulus features and cognitive/affective factors influence an observer's attention. However, the relationship between stimulus-driven (“bottom-up”) and cognitive/affective (“top-down”) factors remains controversial: Can affective salience counteract strong visual stimulus signals and shift attention allocation irrespective of bottom-up features? Is there any difference between negative and positive scenes in terms of their influence on attention deployment? Here we examined the impact of affective factors on eye movement behavior, to understand the competition between visual stimulus-driven salience and affective salience and how they affect gaze allocation in complex scene viewing. Building on our previous research, we compared predictions generated by a visual salience model with measures indexing participant-identified emotionally meaningful regions of each image. To examine how eye movement behaviour differs for negative, positive, and neutral scenes, we examined the influence of affective salience in capturing attention according to emotional valence. Taken together, our results show that affective salience can override stimulus-driven salience and overall emotional valence can determine attention allocation in complex scenes. These findings are consistent with the hypothesis that cognitive/affective factors play a dominant role in active gaze control.